Mid-infrared grayscale metasurface holograms - Wu, Kedi (2021)
Optical metasurfaces composed of two-dimensional arrays of densely packed nanostructures can project arbitrary holographic images at mid-infrared frequency. Our approach employs silicon nanopillars to control light properties, including polarization-independent phase response working with high-transmission efficiency over the 2π-phase modulation range at wavelength 4.7 μm. We experimentally dispose nanopillars accordingly to phase-only profiles calculated using the conventional Gerchberg-Saxton algorithm and revealed the optical performances of our devices using a mid-infrared on-axis optical setup. The total efficiency of our reflection hologram reaches 81%. Our experimental results agree well with the image of the desired object, opening up new perspectives for mid-infrared imaging and displaying for military, life science and sensing application.